PEMBUATAN APLIKASI ECOMMERCE, PACKAGING DESIGN DAN MANAJEMEN PEMASARAN UNTUK USAHA KULINER KOTA BATAM - Muhammad Rasid Ridho; Pastima Sima; Desrini Ningsih (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
Culinary business is very developed in the City of Batam, especially the majority of the community is workers. Because not have no time to cook, citizens prefer to buy food outside while relaxing with the family. Demand more and more, more and more are also opened businesses in the culinary field, so the competition in selling gain weight. Both partners cake tape miss and toteles donuts still does not have an ecommerce, not to have the packaging design and marketing is still lacking. The purpose of this activity is to create an ecommerce, create packaging design and marketing of products. Ecommerce into one solution to improve a positive image to the community of Batam. The design of the packaging (packaging design) exciting the attention of his own for the buyer. Taste indeed determine the purchase back, with a pretty look is expected to add a positive value in the eyes of the customer by creating a unique form as well as print different layouts. The factor of economic withlooking so packaging does not need the expensive cost. Marketing management by providing coaching to be able to maintain business continuity as well as remain attentive to the satisfaction of the buyer. The results of these activities are already making a second web of partners, is already making packaging design and development marketing.